The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1002/smll.201402890
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Processed Large‐Area Nanocrystal Arrays of Metal–Organic Frameworks as Wearable, Ultrasensitive, Electronic Skin for Health Monitoring

Abstract: Pressure sensors based on solution-processed metal-organic frameworks nanowire arrays are fabricated with very low cost, flexibility, high sensitivity, and ease of integration into sensor arrays. Furthermore, the pressure sensors are suitable for monitoring and diagnosing biomedical signals such as radial artery pressure waveforms in real time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 40 publications
1
62
0
Order By: Relevance
“…Moreover, the micro-structured e-skin can attach onto the wrist and detect the wrist pulse caused by blood pressure (Fig.7f). As shown in Fig.7g, three typical peaks assigned to early systolic peak pressure (P 1 ), late systolic peak pressure (P 2 ) and diastolic pulse waveform (P 3 ) are observed, 5,50 demonstrating the eskin owns low detection limit and may be a robust candidate in physiological diagnosis. By tailoring the micro-structured PDMS conductor with size of 0.5 cm × 0.5 cm and attaching the smaller size e-skins onto PET film (thickness: 100 μm), a piezoresistive pressure sensor array with 3 × 3 pixels is fabricated.…”
Section: Performance Of the Flexible E-skinmentioning
confidence: 95%
“…Moreover, the micro-structured e-skin can attach onto the wrist and detect the wrist pulse caused by blood pressure (Fig.7f). As shown in Fig.7g, three typical peaks assigned to early systolic peak pressure (P 1 ), late systolic peak pressure (P 2 ) and diastolic pulse waveform (P 3 ) are observed, 5,50 demonstrating the eskin owns low detection limit and may be a robust candidate in physiological diagnosis. By tailoring the micro-structured PDMS conductor with size of 0.5 cm × 0.5 cm and attaching the smaller size e-skins onto PET film (thickness: 100 μm), a piezoresistive pressure sensor array with 3 × 3 pixels is fabricated.…”
Section: Performance Of the Flexible E-skinmentioning
confidence: 95%
“…However, complicated preparation procedures involving photolithographic equipment and high-resolution templates were expensive and hard to reproduce in large area www.advelectronicmat.de production, which significantly limited the practical use of flexible sensing devices. [101] Until now, it remains a challenge to achieve highly sensitive and large area sensor arrays on easyprocessing active materials with facile fabrication method and simple device structures. To address this issue, our group reported that through facile and cost-effective solution process, ultrasensitive electronic skins based on copper 7,7,8,8-tetracyano-p-quinodimethane (CuTCNQ) nanocrystal arrays with large area could be fabricated.…”
Section: How To Improve the Performance Of Sensors Through Nanoassembmentioning
confidence: 99%
“…To address this issue, our group reported that through facile and cost-effective solution process, ultrasensitive electronic skins based on copper 7,7,8,8-tetracyano-p-quinodimethane (CuTCNQ) nanocrystal arrays with large area could be fabricated. [101] CuTCNQ nanowire arrays were fabricated as described in Figure 5A. First, 200 nm copper thin film was thermally evaporated onto precut 25 µm thick polyimide (PI) flexible substrate.…”
Section: How To Improve the Performance Of Sensors Through Nanoassembmentioning
confidence: 99%
“…[3] In particular,f unctionalp olymers with high strength,s tretchability, self-healing, and conductivity have been fabricated for E-skin applications. [4] To furtherd evelopE -skin with desired mechanical properties and multifunctionalities, active materials, such as metal nanoparticles, [3a] graphene oxide, [5] carbonn anotubes, [6] organic microspheres, [7] and metal-organic frameworks, [8] have been incorporatedi nto the polymers for E-skin fabrication.F or example,B ao and co-workers successfully fabricated conductive micronickel-particle-reinforced electronic sensor skin. [3a] Humanp rotein-based hybrid hydrogels incorporatedw ith graphene oxide nanoparticles wered eveloped by Wang et al, through the incorporation of GO nanoparticles to improve both toughness and elasticity of the engineered hydrogels.…”
Section: Introductionmentioning
confidence: 99%